Tourist activity in coral reefs of the Natural National Park Corals of Rosario and San Bernardo, Colombia. - Castro Triana, Luz Ayda (2016)
slas del Rosario and San Bernardo is a National Nature Park that protects coral reefs and mangroves but is increasingly affected by tourism. Between April 2011 and January 2013 we interviewed users of the 16 main submarine trails. The most frequented trail was Ministerio / Acuario mío (23,7 ± 5,7 %); Open Water scuba diving was the main diving certificate among tourists (63,5 ± 4,5 %); 58.6% lacked basic diving experience, and 74% had some type of contact with the corals (mostly hard coral: 0,9 ± 0,05). An average there were 5,39 contacts per diver (scuba). For basic diving there was an average of 0.18 contacts/ min/ diver. Diving causes direct and indirect damages to these ecosystems. Most coral contacts are from inexperienced divers: training the tourists is fundamental.